The emerging female citizen : gender and enlightenment in Spain - Smith, Theresa Ann, 1971- (Studies on the history of society and culture ;, 2006)
In analysing the meaning of women's presence in these diverse centres of the Enlightenment, Smith offers a new interpretation of the dynamic relationships among political discourse, social action, and gender ideologies.